Ответы 2

  • Ответ:

    18/19-(8/19+(14/19-x))=2/19

    18/19-8/19-14/19+x-2/19=0

    x=6/19

    Пошаговое объяснение:

  •  \frac{18}{19}  - ( \frac{8}{19}  +  \frac{14}{19}  - x) =  \frac{2}{19}  \frac{18}{19}  - ( \frac{22}{19} - x ) =  \frac{2}{19}  \frac{18}{19}  -  \frac{22}{19} + x =  \frac{2}{19}   -  \frac{4}{19}  + x =  \frac{2}{19} x =  \frac{2}{19}  +  \frac{4}{19} x =  \frac{6}{19}
    • Автор:

      tuffy
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years